Evaluation of patient engagement in medicine development: A multi‐stakeholder framework with metrics - Lidewij Eva Vat; Teresa Finlay; Paul Robinson; Giorgio Barbareschi; Mathieu Boudes; Ana Maria Diaz Ponce; Michaela Dinboeck; Lukas Eichmann; Elisa Ferrer; Sevgi E. Fruytier; Claudia Hey; Jacqueline E. W. Broerse; et al. (Wiley, 2021)
Abstract Background Patient engagement is becoming more customary in medicine development. However, embedding it in organizational decision‐making remains challenging, partly due to lack of agreement on its value and the means to evaluate it. The objective of this project was to develop a monitoring and evaluation framework, with metrics, to demonstrate impact and enhance learning. Methods A consortium of five patient groups, 15 biopharmaceutical companies and two academic groups iteratively created a framework in a multi‐phase participatory process, including analysis of its application in 24 cases. Results The framework includes six components, with 87 metrics and 15 context factors distributed among (sub)components: (a) Input: expectations, preparations, resources, representativeness of stakeholders; (b) Activities/process: structure, management, interactions, satisfaction; (c) Learnings and changes; (d) Impacts: research relevance, study ethics and inclusiveness, study quality and efficiency, quality of evidence and uptake of products, empowerment, reputation and trust, embedding of patient engagement; (e) Context: policy, institutional, community, decision‐making contextual factors. Case study findings show a wide variation in use of metrics. There is no 'one size fits all' set of metrics appropriate for every initiative or organization. Presented sample sets of metrics can be tailored to individual situations. Conclusion Introducing change into any process is best done when the value of that change is clear. This framework allows participants to select what metrics they value and assess to what extent patient engagement has contributed. Patient contribution Five patient groups were involved in all phases of the study (design, conduct, interpretation of data) and in writing the manuscript.